2015
DOI: 10.1590/1809-4430-eng.agric.v35n6p1093-1104/2015
|View full text |Cite
|
Sign up to set email alerts
|

‘Sweet grape’ tomato post harvest packaging

Abstract: This paper aims at evaluating the shelf life of mini tomatoes (Lycopersicum esculentum Mill.) cultivar 'Sweet Grape', grown in hydroponics, and stored under environmental and refrigerated conditions inside different packages. We adopted a completely randomized design, in which treatments were combinations of storage conditions: environment (e) and refrigerated (r) with packaging: polyvinyl chloride film (PVC); low-density polyethylene (LDPE); biofilm of tomato fruit of Solanum lycocarpum A.St.-Hil (lobeira) (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…Consequently, the samples with more weight loss (control) depicted greater reduction in their firmness. Similar results were reported by Gharezi et al (2012) and Sandri et al (2015).…”
Section: Firmnesssupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, the samples with more weight loss (control) depicted greater reduction in their firmness. Similar results were reported by Gharezi et al (2012) and Sandri et al (2015).…”
Section: Firmnesssupporting
confidence: 91%
“…Consequently, the samples with more weight loss (control) depicted greater reduction in their firmness. Similar results were reported by Gharezi et al () and Sandri et al (). The fruits stored in PP were more firm followed by LDPE and PBNC packages (Figure c,d) but their overall effect was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors observed loss of fresh tomato mass throughout storage, but there was no control of the exchange of gases and water vapor with the environment (TOLESA & WORKNEH, 2017). Sandri et al (2015), in the study of different storage conditions, observed that when the fruits were packed in packages that allowed the exchange of gases with the environment, they also presented a loss of fresh mass greater than the fruits stored in packages that did not allow or that decreased the exchange of gases, thus corroborating the results observed in this study.…”
Section: Physical-chemical Characteristicssupporting
confidence: 88%
“…By studying fruits of the commercial hybrid sweet grape in several types of packaging, especially the flexible plastic films of PVC (polychloride of vinyl) and LDPE (low-density polyethylene), Sandri et al (2015) observed the maintenance of pH values in open packages, which offered no barrier to gas exchange. In sealed plastic film packaging, they also observed a slight tendency to increase pH, although lower than those observed in the present study.…”
Section: Physical-chemical Characteristicsmentioning
confidence: 99%
“…Cherry-or mini-tomatoes have been stood out among tomato types that have been showing high demand for fresh consumption (Guilherme et al, 2014), mainly those from special hybrids, such as the sweet-grape tomato. The main characteristics of sweet-grape tomatoes is low acidity index, high contents of sugar and soluble solids (Junqueira et al, 2011), small size, elongated shape, and intense red color, which ensure a good acceptability by consumers (Oltman et al, 2014) and results in a high consumption, making the crop economically viable (Sandri et al, 2015). Fruits from this hybrid represents up to 10% of the total horticulture sales, despite being 20% to 40% more expensive than those from common tomato types (Junqueira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%